Protective effect of isosteviol sodium against LPS-induced multiple organ injury by regulating of glycerophospholipid metabolism and reducing macrophage-driven inflammation. (October 2021) - Wang, Shanping; Tan, Keai Sinn; Beng, Huimin; Liu, Fei; Huang, Jiandong; Kuai, Yihe; Zhang, Rui; Tan, Wen
Abstract: Sepsis is a severe inflammatory disorder that can lead to multiple organ injury. Isosteviol sodium (STV-Na) is a terpenoid derived from stevioside that exerts anti-inflammatory, antioxidant and antiapoptotic activities. However, the influence of STV-Na on sepsis remains unknown. Here, we assessed the potential effects of STV-Na on sepsis and multiple organ injury induced by lipopolysaccharide (LPS). We found that STV-Na increased the survival rate of mice treat with LPS, significantly improved the functions of the heart, lung, liver, and kidney, reduced the production of inflammatory cytokines and decreased macrophage infiltration. Moreover, Multiorgan metabolomics analysis demonstrated that glutathione metabolism, purine metabolism, glycerophospholipid metabolism and pantothenate and CoA biosynthesis, were significantly altered by STV-Na. This study provides novel insights into the metabolite changes of multiple organ injury in septic mice, which may help characterize the underlying mechanism and provide an improved understanding of the therapeutic effects of STV-Na on sepsis. Graphical Abstract: ga1